Developing a protocol for ankle sprain rehabilitation in elite court sports - Ward, T.; Smyth, E. (Australian Conference of Science and Medicine in Sport and Third National Sports Injury Prevention Conference: 2003. Tackling the barriers of performance and participation, 2003)
A retrospective study on the current management of ankle injuries was conducted at the AIS during 2001. The study selectively examined 3 court sports: Netball (N), Men`s Basketball (MB) and Women`s Basketball (WB). Method: Data collected by the initial treating physiotherapist and throughout the athlete's return to sport, was tabulated and examined at the end of the scholarship year. Results: In total there were 41 ankle injuries (N= 13, MB= 19, WB= 9). Of significance were 19 injuries in MB (53% of team). With appropriate management, athletes returned to full training within 5.7 days on average (N= 6.7, MB= 4.3, WB= 6.0). However, total training lost for all sports was 223 days. Within a 3-month period 13 ankle injuries had reoccurred. A 21-day rehabilitation program was implemented among other prevention strategies in 2002. The program was based on functional requirements for returning to sport and used current ideas found in an extensive literature review on ankle rehabilitation. Total ankle injuries dropped by 20 to 21 (N=8, MB=7, WB=6). Importantly, for coaches, training days lost correspondingly reduced from 223 to 119. Use of this rehabilitation program accounted for a reduction in repeated injuries; from 13 to 5, and to date in 2003 there have been no repeated ankle injuries. Conclusion: The 21-day rehabilitation program has dramatically reduced ankle re-injury. The use of this sport specific rehabilitation has provided training structure and improved athlete compliance. The protocol of acute ankle management is now compatible with elite athlete training.